Effects of sticky rice on the carbonation reaction of lime-treated soil in earthen sites. (16th May 2023) - Fan, Wenjun; Chen, Wenwu; Zhang, Qiyong; Wu, Guocheng
Highlights: Sticky rice can inhibit the carbonation reaction of lime-treated soil. The outer part of the sample had a higher carbonation than the inner part. Binding and inhibition effects of sticky rice adjusted strength of lime-treated soil. Abstract: Earthen sites with important historical, artistic, social, cultural, and scientific values have suffered serious damage due to long-term influences from various natural factors. The sticky rice and lime composite shows the potential to be applied to the protection of earthen sites. The carbonation of lime has a significant impact on the engineering properties of earthen sites. The main purpose of this study is to investigate the effect of sticky rice on the carbonation reaction of lime-treated soil in earthen sites. The results indicated that sticky rice can inhibit the carbonation reaction of lime, resulting in a reduced calcium carbonate content. The inhibition effect of sticky rice on carbonation reaction of lime could be attributed to the limitation of gaseous water and CO2 gas diffusion. Sticky rice had both binding effect and inhibition effect on lime-treated soil, and its mechanical properties depended on the dominant effect after these effects cancelled each other. When the lime content was ≤6%, the addition of sticky rice can increase the strength of soil. When the lime content was >6%, however, the addition of sticky rice resulted in a decrease in strength. In addition, the carbonation of the outside of the cylindrical sample was higher than that of the inside. These findings can increase the understanding of protecting earthen sites with sticky rice and lime composite, and optimize the application of sticky rice and lime composite.